Anti-depressive effects of Jiao-Tai-Wan on CORT-induced depression in mice by inhibiting inflammation and microglia activation. (30th January 2022) - Bai, Guiqin; Qiao, Yiqi; Lo, Po-Chieh; Song, Lei; Yang, Yuna; Duan, Lining; Wei, Sufen; Li, Min; Huang, Shuiqing; Zhang, Beiping; Wang, Qi; Yang, Cong
Abstract: Ethnopharmacological relevance: Jiao-Tai-Wan (JTW) is a very famous traditional Chinese medicine formula for the treatment of psychiatric disorders, especially in anxiety, insomnia and depression. However, its molecular mechanism of treatment remains indistinct. Aim of the study: We aimed to reveal the action mechanism of JTW on anti-depression via inhibiting microglia activation and pro-inflammatory response both in vivo and in vitro. Material and methods: The corticosterone (CORT)-induced depression mouse model was used to evaluate the therapeutic efficacy of JTW. Behavioral tests (open field, elevated plus maze, tail suspension and forced swim test) were conducted to evaluate the effect of JTW on depressive-like behaviors. The levels of inflammatory factors and the concentration of neurotransmitters were detected by RT-qPCR or ELISA assays. Then three hippocampal tissue samples per group (Control, CORT, and JTW group) were sent for RNA sequencing (RNA-seq). Transcriptomics data analysis was used to screen the key potential therapeutic targets and signaling pathways of JTW. Based on 8 bioactive species of JTW by our previous study using High-performance liquid chromatography (HPLC) analysis, molecular docking analyses were used to predict the interaction of JTW-derived compounds and depression targets. Finally, the results of transcriptome and molecular docking analyses were combined to verify the targets, key pathways, and efficacy of JTW treatment in vivo and vitro. Results: JTW ameliorated CORT-induced depressive-like behaviors, neuronal damage and enhanced the levels of monoamine neurotransmitters in the serum of mice. JTW also inhibited CORT-induced inflammatory activation of microglia and decreased the serum levels of interleukin- 6(IL-6) and interleukin- 1β (IL-1β) in vivo. Transcriptomic data analysis showed there were 10 key driver analysis (KDA) genes with the strongest correlation which JTW regulated in depression mice. Molecular docking analysis displayed bioactive compound Magnoflorine had the strongest binding force to the key gene colony-stimulating factor 1 receptor (CSF1R), which is the signaling microglia dependent upon for their survival. Meanwhile, CSF1R staining showed it was consistent with inflammatory activation of microglia. Our vitro experiment also showed JTW and CSF1R inhibitor significantly reduced lipopolysaccharide (LPS)/interferon-gamma (IFNɣ)-induced inflammatory activation response in macrophage cells. Conclusions: Our study suggests that JTW might ameliorate CORT-induced neuronal damage in depression mice by inhibiting CSF1R mediated microglia activation and pro-inflammatory response. Graphical abstract: Image 1 Highlights: The strategy based on transcriptomics, molecular docking and pharmacological experiment was firstly applied to Jiao-Tai-Wan. Molecular docking displayed the bioactive compound Magnoflorine had the strongest binding force to the key gene CSF1R. Jiao-Tai-Wan might ameliorate neuronal damage in depression mice by inhibiting inflammation and microglia activation.